Relationship between health literacy, preventive behavior, and non-communicable disease risk in urban communities - Evi Nurmaisa Biduri; Cantika Suci Adlina; Fitri Windayani (Edukasi Ilmiah Indonesia, 2026)
Introduction: Non-communicable diseases (NCDs) remain a leading cause of premature morbidity and mortality worldwide, particularly in rapidly urbanizing communities where unhealthy lifestyles and limited health literacy increase disease risk. Although health literacy has been recognized as an important determinant of health, the behavioral mechanisms through which it influences NCD risk remain insufficiently understood. This study aimed to examine the relationships between health literacy, preventive behavior, and NCD risk among adults living in urban communities and to determine the mediating role of preventive behavior. Research Methodology: An analytical cross-sectional study was conducted among 450 adults residing in urban communities of Konawe Regency, Southeast Sulawesi, Indonesia. Participants were selected using multistage probability sampling. Health literacy, preventive behavior, and NCD risk were measured using validated instruments. Structural Equation Modeling (SEM) with SmartPLS 4.0 was applied to evaluate the measurement and structural models. Direct, indirect, and total effects were estimated using bootstrapping with 5,000 resamples, and statistical significance was established at p < 0.05. Results: The measurement model demonstrated satisfactory reliability and validity (Cronbach's α = 0.87–0.92, Composite Reliability = 0.90–0.94, AVE = 0.60–0.68). Health literacy showed a significant positive association with preventive behavior (β = 0.724, 95% CI: 0.648–0.793; p < 0.001) and a significant direct negative association with NCD risk (β = −0.214, 95% CI: −0.357 to −0.082; p = 0.003). Preventive behavior exerted the strongest negative effect on NCD risk (β = −0.531, 95% CI: −0.639 to −0.422; p < 0.001). The indirect effect of health literacy on NCD risk through preventive behavior was statistically significant (β = −0.384, 95% CI: −0.461 to −0.302; p < 0.001), indicating partial mediation. Conclusion: Health literacy contributes to reducing NCD risk primarily by promoting healthier preventive behaviors. Strengthening health literacy should therefore be integrated into community-based NCD prevention strategies alongside interventions that support sustainable healthy lifestyles. These findings provide evidence for developing health policies that combine health literacy improvement with behavioral interventions to reduce the growing burden of NCDs in urban populations.